Calculation of distributed property for deceased person base on faraid rules (focus on death husband) / Noorbaizura Hj Bakar - Hj Bakar, Noorbaizura (2004)
Islam is the way of life. Islam is a religion that covers all aspects in life, where here means a life in the real world and also in the day after. In Islam, Allah has its rules and all the rules that are made by Allah have its own advantages to people in their daily life before and also after their death. Because of this reason, Islam has stated a fair system in distributing the property to the rightful heirs. This is important in order to ensure all the family members especially to the heritance, get the right share of the inheritance property. Faraid is a knowledge that many people easy to forget because they do not know and take this knowledge as an important knowledge to learn. Usually, people or someone like to know or learn the knowledge when there are a person death and the property of the death person need to be distribute among the heir. This situation should not happen and this knowledge should be learn continuously in order to protect people from misunderstand where the death occur. In this project paper, I will make a calculation of distributed property for decease person that base on faraid rules. The faraid knowledge and rules are big. In this rules, there are 25 person involve and known as heritance. But for my project paper, there are 5 people involve where this calculation is made for husband deaths only with his heir are his wife, son (of his wife), daughter (of his wife), mother and father. I hope, this project system can help people especially to the people who interested in learning and knowing the Faraid Law. Although this project system is built for a small quantity of heirs but in the future there will be much more addition in the calculation system in order to make it as a complete system.